RESEARCH ON THE IMPACT OF SOCIAL MEDIA ON BUSINESS/STARTUPS - Shalaka Sajane; Dr. Hemlata Gaikwad (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2021)
Television, newspapers, and radio were the only forms of media available to companies until the late 1990s; however, in the early 2000s, a media revolution occurred, and the world was introduced to Social Media. Like any other kind of media, social media is a tool for communication, but it is utilized on a wider scale for social engagement utilizing highly accessible and scalable technologies. Techniques of communication Social media has a beneficial impact and influence on both the business and its clients. Marketers are increasingly relying on social media, which requires relatively little effort. Consumers in today's world consider a company's internet presence before making a decision.As a result, businesses may innovate while still building a strong social presence by continually attending to their consumers' wants and concerns. Companies have accepted Social Media as a vital tool for their marketing campaigns on a global scale; however, this is not the case in India. What are the advantages of using social media? What are some social media examples? This research examines the advantages, consequences, and significance of social media on company performance and growth.